2017
DOI: 10.3390/met7090367
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Powder Surface Contamination in the Ni-Based Superalloy Alloy718 Fabricated by Selective Laser Melting and Hot Isostatic Pressing

Abstract: The aim of this study was to gain a deep understanding of the microstructure-mechanical relationship between solid-state sintering and full-melting processes. The IN718 superalloy was fabricated by hot isostatic pressing (HIP) and selective laser melting (SLM). Continuous precipitates were clearly localized along the prior particle boundary (PPB) in the HIP materials, while SLM materials showed a microstructure free of PPB. The mechanical properties of specimens that underwent SLM + solution treatment and agin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…1b). Note that this is consistent with earlier made observations [1,3,4,7,8]. Large carbides with a size of 1-10 μm usually observed in the industrial Inconel 718 superalloy [20] were not revealed in the SLM superalloy.…”
Section: Microstructure Of the Superalloy Obtained By Slmsupporting
confidence: 93%
See 3 more Smart Citations
“…1b). Note that this is consistent with earlier made observations [1,3,4,7,8]. Large carbides with a size of 1-10 μm usually observed in the industrial Inconel 718 superalloy [20] were not revealed in the SLM superalloy.…”
Section: Microstructure Of the Superalloy Obtained By Slmsupporting
confidence: 93%
“…The grains shown in (a) consisted of subgrains (b). The γ'' phase precipitates are visible at high magnifications in the interior of subgrains [8].…”
Section: Microstructure Of the Superalloy Obtained By Slmmentioning
confidence: 98%
See 2 more Smart Citations
“…This excessive grain growth did not occur alongside NbC dissolution in heat-treated compacted powder specimens due to the presence of prior particle boundaries (PPB) restricting the growth of grains [35]. However, SLM-manufactured IN718 specimens are free of PPBs [37]. Without PPBs inhibiting grain growth, Ostwald ripening of NbC precipitates is expected to lead to excessive grain coarsening in heat treated SLM specimens.…”
Section: Microstructural Development Of Heat Treated Inconel 718mentioning
confidence: 99%